2015
DOI: 10.1371/journal.pone.0129156
|View full text |Cite
|
Sign up to set email alerts
|

Biopersistence of PEGylated Carbon Nanotubes Promotes a Delayed Antioxidant Response after Infusion into the Rat Hippocampus

Abstract: Carbon nanotubes are promising nanomaterials for the diagnosis and treatment of brain disorders. However, the ability of these nanomaterials to cross cell membranes and interact with neural cells brings the need for the assessment of their potential adverse effects on the nervous system. This study aimed to investigate the biopersistence of single-walled carbon nanotubes functionalized with polyethylene glycol (SWCNT-PEG) directly infused into the rat hippocampus. Contextual fear conditioning, Y-maze and open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Others evaluated SWCNT cytotoxicity using THP1 monocytes and showed that SWCNTs were cytotoxic to THP1 cells grown in 2D cell culture conditions but were not cytotoxic to cells grown in the 3D tissue-mimetic model(Movia et al, 2011). PEG functionalized SWCNTs also did not induce significant morphological alterations in rat hippocampus(Dal Bosco et al, 2015). Similarly, we found that DSPE-PEG coated, acid oxidized MWCNTs were cytotoxic to glioblastoma cells grown in two-dimensional monolayer, but had no observable effect on growth of glioblastoma cells grown as three-dimensional spheroids(Eldridge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Others evaluated SWCNT cytotoxicity using THP1 monocytes and showed that SWCNTs were cytotoxic to THP1 cells grown in 2D cell culture conditions but were not cytotoxic to cells grown in the 3D tissue-mimetic model(Movia et al, 2011). PEG functionalized SWCNTs also did not induce significant morphological alterations in rat hippocampus(Dal Bosco et al, 2015). Similarly, we found that DSPE-PEG coated, acid oxidized MWCNTs were cytotoxic to glioblastoma cells grown in two-dimensional monolayer, but had no observable effect on growth of glioblastoma cells grown as three-dimensional spheroids(Eldridge et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study , the fluorescence emission of isolated SWCNTs appears in the 900‐nm to 1400‐nm range, greater than the emission wavelength used in the present study. In addition, no interference from pegylated SWCNTs was observed in H 2 DCF‐DA fluorescence generation . The ROS area was standardized by the number of viable cells, and ROS levels were expressed in terms of fluorescence area, where the area was obtained by integrating the fluorescence units (FU) over the measurement time (90 min) and expressed as FU/min.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in vitro studies have confirmed that exposure to different CNTs causes oxidative damage and increases ROS in a cell type–dependent manner. Moreover, SWCNTs functionalized with polyethylene glycol (SWCNT‐PEG) and directly infused into rat hippocampus reduced ROS and induced antioxidant defenses 7 d after injection, suggesting that the biopersistence of nanomaterial in the tissue can induce an antioxidant response .…”
Section: Introductionmentioning
confidence: 99%
“…PEGylated SWCNTs exhibited increased biopersistence in the tissue and could initiate a delayed antioxidant defense after administration into the rat hippocampus. [179]…”
Section: (8 Of 24)mentioning
confidence: 99%